Perencanaan Strategi Pemasaran (Segmentation, Targetting dan Positioning) Koran Harian Solopos Berdasarkan Persepsi Konsumen - Zakaria, Roni; Fahma, Fakhrina; Astuti, Elisa Reinni (Performa: Media Ilmiah Teknik Industri, 2005)
Wide scope of the newspaper circulation not further becomes increased values that can be stronger the market. When the newspaper likely cone be “attendant” a limited community (local), newspaper will to try appear as superior and established in market community that will be reach. The research is done to know segments, target and position of Solopos newspaper as the basic of their marketing strategies. Data intrepetation is done through survey with questioner methods that spread to Solopos’s customer in fifthten village chief in Surakarta. The methods of processing data using multivariate analysis i.e. cluster analysis uses to find out the customers’ group based on their similar perception, Multi Dimensional Scaling Analysis and Correspondence Analysis used to mapping the position of Solopos among its competitor. Output of this research is that Solopos customer grouping into three segments, with different characteristics i.e. occupation, income, and position in family. First segment consist of customer which has more interest on news completely, style language, price agree with quality and easy to get its. Respondent in second segment inclined negative characteristic to some part of the attribute. Third segment more interest on headline, actuality, factuality, and inexpensive price and appropriate to ship the product. Position mapping show that the position of brand’s point is far from each other. It means that customer’s perception on each newspaper is differently or each brand has its uniqueness. Furthermore, known that Solopos has specialty on service and promotion. Based on the result of data analysis, Solopos would be able to be offered for community’s group of first and third segment, because of the specialty that is service. The design of marketing mix includes maintaining the quality and price, increasing the promotion and service that are Solopos’s specialty.